The Significance of Hounsfield Unit and Tumor Diameter in the Differentiation of Malignant and Benign Adrenal Masses - Ozgul, Halit; Yildiz, Turan Can; Cakir, Remzi Can; Canturk, Semih; Celik, Omer; Yur, Mesut; Alparslan, Ahmet Sukru (Galenos Publ House, 2024)
Aim: The Hounsfield unit (HU) used in non-contrast computed tomography (CT) imaging can predict adrenal masses. In the literature, a HU measurement of >10 on non-contrast CT has been reported to have a wide range of sensitivity (33-72%) in detecting malignancy in patients with adrenal masses, and the size of malignant masses is >4 cm in approximately 90% of cases. The current study investigated the role of the HU value and tumor diameter measured on preoperative CT imaging in the differentiation of benign and malignant masses. Methods: Data analysis was conducted on patients undergoing adrenalectomy for adrenal masses at two different tertiary care centers between January 1, 2019 and January 1, 2023. Patients who underwent an adrenalectomy non-contrast CT scans were assessed for HU and tumor size. The patients were divided into two groups according to histopathologically confirmed benign or malignant masses. Statistical analysis, including receiver operating characteristic curve assessment, was performed to evaluate the diagnostic accuracy. Results: The study included 108 patients, of whom 66.7% (n=72) were female and 33.3% (n=36) were male. The mean age was 51.01 +/- 14.01 years. The laparoscopic technique was used in 72 patients, the robotic technique in 17, and the open technique in 19. The mean length of hospital stay was 4 (2-37) days. The mean tumor size was 55 (10-230) mm. The mean operative time was 80 (50-180) minutes. The mean amount of intraoperative blood loss was 40 (20-300) milliliters. The surgical method, tumor diameter, operative time, amount of intraoperative blood loss, and HU value of the mass statistically significantly differed between the groups (p<0.001). We found that the cut-off values of HU and tumor diameter for distinguishing malignant masses from benign masses were 30.5 and 72.5 mm, respectively. At a cut-off value of 30.5 or above, HU had a sensitivity of 100% and a specificity of 81.6% in identifying malignant masses, whereas a sensitivity of 100% and a specificity of 88.7% were determined for malignant masses with a tumor size of 72.5 mm or above. Conclusion: The HU value and tumor diameter were crucial for distinguishing between benign and malignant adrenal masses, enhancing diagnostic accuracy, and informing treatment decisions.
Keywords: Adrenal mass; Hounsdield unit; diameter of tumor